Upgrading Strategies in Disagreement among Indonesian EFL Learners - Choyimah, Nurul (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This study was aimed at finding out the patterns of relationship between English language proficiency levels and upgrading strategies in disagreement by using conversation analysis. Students taking the Seminar on Linguistics course in the School of Cultural Studies at Brawijaya University were selected as the subjects of this study. They were classified into pre-intermediate, intermediate, pre-advanced, and advanced proficiency levels. The results of the analysis show that the students performed both direct and indirect disagreement, each of which resulted in different upgrading strategies. Pre-intermediate, intermediate, and pre-advanced students predominantly used the double-negation strategy. Students at the advanced level never performed direct disagreement. Indirect disagreement used by students across all proficiency levels was dominated by the use of the you strategy.